(untitled) (Journal of Engineering, 2005)
In this paper, the transient flow in a rectangular open channel has been studied for different conditions. The velocity and depth of water have been calculated at different sections in the channel. A computer program (Channel) was developed to solve the mathematical model using characteristic method .The initial conditions have been calculated using Runge-Kutta method.